If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n + 9 = 4 + -4(2n + -11) Reorder the terms: 9 + 5n = 4 + -4(2n + -11) Reorder the terms: 9 + 5n = 4 + -4(-11 + 2n) 9 + 5n = 4 + (-11 * -4 + 2n * -4) 9 + 5n = 4 + (44 + -8n) Combine like terms: 4 + 44 = 48 9 + 5n = 48 + -8n Solving 9 + 5n = 48 + -8n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '8n' to each side of the equation. 9 + 5n + 8n = 48 + -8n + 8n Combine like terms: 5n + 8n = 13n 9 + 13n = 48 + -8n + 8n Combine like terms: -8n + 8n = 0 9 + 13n = 48 + 0 9 + 13n = 48 Add '-9' to each side of the equation. 9 + -9 + 13n = 48 + -9 Combine like terms: 9 + -9 = 0 0 + 13n = 48 + -9 13n = 48 + -9 Combine like terms: 48 + -9 = 39 13n = 39 Divide each side by '13'. n = 3 Simplifying n = 3
| 1/3(1-x)-(x+1)/2=-2 | | 6.46+2.3x=1.24x-7 | | 129=3(1+7v) | | .2y-3=.5 | | G(-2)=4(-2)-3 | | (9x-3)/6=5/2 | | y/5-7=-2 | | t^2/2+t^2 | | 13a-45+a= | | 4x+4x(.05)=105.00 | | 62.9296(y-100)+64.9278y=63.546 | | -286=4(1+8r)+2r | | 4x+8=x | | 3(x+5)(x+5)=60 | | 2h+9=-2+3(3h+6) | | x+0.3=11 | | 3x+17=7x-5 | | -9-(4+10)+20= | | -2.3=2.4z+1.3 | | 8y+7=1-2(3y-3) | | 3.9m-4.2=-1.1(4m+8) | | F(5)=-2(5)+3 | | 180=-6(4v+2) | | 62.9296(100-y)+64.9278y=63.546 | | x^4-12x^3-38x^2+300x-275=0 | | 7y+2x+3=20+2x | | 9x-3=5/2 | | 3x+4/7-5x-3/7=6/7 | | F(5)=-2x+3 | | 9x^2-61x+4=0 | | 3-4x/5=-9 | | 5(3r-1)-(r-1)=1+5+3r-5 |